2023
DOI: 10.1002/hsr2.1322
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in lipid and hormonal titers in patients with acne and their relationship with severity: A case‐control study

Abstract: Background and Aims Acne is a frequently diagnosed skin condition that causes pilosebaceous apparatus clogs and/or inflammatory responses in the majority of teenagers. It is a multifactorial disease that can develop due to various factors. We aimed to evaluate lipid profiles and hormonal levels in patients with acne and correlate them to acne severity. We also aim to explore the alteration of lipid profiles and hormonal levels and their effect on the occurrence of acne. Methods A case‐control study was perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…14 In our population, several studies have been conducted to understand the relationship between genetic factors and dermatological conditions. [15][16][17][18][19][20][21][22][23][24] However, according to our knowledge, no study tries to determine the mechanisms by which miRNAs contribute to AA.…”
Section: Introductionmentioning
confidence: 99%
“…14 In our population, several studies have been conducted to understand the relationship between genetic factors and dermatological conditions. [15][16][17][18][19][20][21][22][23][24] However, according to our knowledge, no study tries to determine the mechanisms by which miRNAs contribute to AA.…”
Section: Introductionmentioning
confidence: 99%
“…Autoimmune processes in AA may be impacted by vitamin D regulation of immune responses through VDR. 5 Several studies in our population have tried to find the relation between different biochemical parameters and different skin diseases such as acne, [6][7][8][9][10] and psoriasis vulgaris [11][12][13][14][15] but according to our knowledge, there is no study able to find the relation between CRP and vitamin D in AA patients.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12][13] Adipose tissue itself also contains both estrogen and androgen receptors. 9,12,13 Studies have shown that patients with acne who consume food that has a lower glycemic load tend to have less lesions than those who consume diets with a higher glycemic load. 10 Weight loss has been shown to improve factors that contribute to both the inflammatory and endogenous factors that contribute to acne.…”
Section: Introductionmentioning
confidence: 99%
“…Acne vulgaris is caused by excessive sebum production, inflammation, follicular hyperkeratinization, or Propionibacterium acnes bacterial colonization of the pilosebaceous unit in the skin. 9…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation